2022
DOI: 10.1016/j.ekir.2021.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Disease After Acute Decompensated Heart Failure

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Our results showed that compared with early AKI recovery, progression to AKD was associated with both 1-year mortality and development of de novo CKD. This is consistent with previously published data conducted amongst patients admitted for cardiovascular reasons, which demonstrated that AKD was associated with both short-(90 days) [40] and long-term (5 years) [41] risk of death and adverse renal events. However, in a cohort of patient admitted for sepsis-associated AKI, individuals with early AKI reversal had similar mortality rates as those developing AKD [42].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that compared with early AKI recovery, progression to AKD was associated with both 1-year mortality and development of de novo CKD. This is consistent with previously published data conducted amongst patients admitted for cardiovascular reasons, which demonstrated that AKD was associated with both short-(90 days) [40] and long-term (5 years) [41] risk of death and adverse renal events. However, in a cohort of patient admitted for sepsis-associated AKI, individuals with early AKI reversal had similar mortality rates as those developing AKD [42].…”
Section: Discussionsupporting
confidence: 93%
“…AKD is considered an important transition period in the AKI-to-CKD continuum (33). The severity of AKD has been reported to be significantly correlated to increased risk of adverse outcomes (14,15,22,(34)(35)(36). However, several previous studies have reported conflicting results (22,33,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The WRF and AKI in AHF are common complications associated with ominous outcomes [ 4 ]. The occurrence of AKI has been estimated at 9–13% of AHF patients [ 16 , 17 ]. The underlying causes of the WRF in AHF are complex and not fully understood; the most prominent hypotheses include the impact of, i.a., congestion [ 18 ].…”
Section: Discussionmentioning
confidence: 99%